Daya Terima Gyoza Tepung Kacang Merah dan Jamur Kuping sebagai Makanan Selingan untuk Remaja Putri Overweight - Dyandra Fayzanadifa; Annis Catur Adi (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
The prevalence of overweight among Indonesian adolescents increased from 7.3% (2013) to 13.5% (2018), partly driven by habitual consumption of high-calorie, high-fat, and low-fiber snacks. This study aimed to analyze the effect of substituting red kidney bean flour in gyoza skin and wood ear mushroom in the filling on organoleptic acceptability and nutritional content as a high-fiber snack for overweight adolescent girls. An experimental study using a Completely Randomized Design (CRD) was conducted with three formulas tested: F0 (control), F1 (30% red kidney bean flour, 50% wood ear mushroom), and F2 (40% red kidney bean flour, 60% wood ear mushroom). Hedonic evaluation was performed by 30 semi-trained panelists and data were analyzed using Friedman and Wilcoxon tests (α=0.05). Nutritional content was assessed through proximate and dietary fiber analysis at the Nutrition Laboratory of FKM Universitas Airlangga. Results showed that substitution significantly affected color, aroma, and texture (p<0.05), but not taste (p=0.299). Formula F1 obtained the highest overall acceptability mean score among modified formulas (3.66), with superior performance in texture (4.30) and taste (3.67). Based on nutritional analysis, F1 contained 3.35 g dietary fiber per serving, 5.38 g fat per serving, and 240 kcal per serving. Formula F1 is recommended as the best formula, providing a balance between organoleptic acceptability and nutritional quality as a high-fiber functional snack for overweight adolescent girls.